The participation of Jordanian women in food security and food production - Shatanawi M.; Naber S.; Al Smadi H.; Al Shneikat G. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
In Jordan, women play an important role in almost all agriculture and livestock activities of the household and in many cases their participation exceeds that of men. The well being of Jordanian women has improved significantly over the past two decades as reflected by their increased (though low) participation in the labor force, higher life expectancy, improved educational attainment and decline in the fertility rate. The national Jordanian strategies call for increasing the role of women's participation in the socio-economic development through training programs. Various NGOs provide training for women as well as income generating projects and loans to enhance their economic independance and participation. The role of women in the management of water resources is very important in countries of extreme water scarcity like Jordan where women in the public sector have demonstrated a high level of performance in the management of irrigation projects and extension services. Although women participate in the socio-economic development, there are some constraints such as the cultural context, the lack of technical support and of women's organizations in rural areas, and the lack of implementation of the participatory approach.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)